Validation of the Amsterdam Beverage Picture Set: A Controlled Picture Set for Cognitive Bias Measurement and Modification Paradigms. (October 2015) - Pronk, Thomas; van Deursen, Denise S.; Beraha, Esther M.; Larsen, Helle; Wiers, Reinout W.
<x xml:space="preserve">Abstract</x> Background Alcohol research may benefit from controlled and validated picture sets. We have constructed the Amsterdam Beverage Picture Set (ABPS), which was designed for alcohol research in general and cognitive bias measurement and modification in particular. Here, we first formulate a position on alcohol stimulus validity that prescribes that alcohol‐containing pictures, compared to nonalcohol‐containing pictures, should induce a stronger urge to drink in heavy drinkers than in light drinkers. Because a perceptually simple picture might induce stronger cognitive biases but the presence of a drinking context might induce a stronger urge to drink, the ABPS contains pictures with and without drinking context. By limiting drinking contexts to simple consumption scenes instead of real‐life scenes, complexity was minimized. A validation study was conducted to establish validity, to examine ABPS drinking contexts, and to explore the role of familiarity, valence, arousal, and control. Methods Two hundred ninety‐one psychology students completed the Alcohol Use Disorders Identification Test, as well as rating and recognition tasks for a subset of the ABPS pictures. Results The ABPS was well‐recognized, familiar, and heavy drinkers reported a greater urge to drink in response to the alcohol‐containing pictures only. Alcohol presented in drinking context did not elicit a stronger urge to drink but was recognized more slowly than alcohol presented without context. Conclusions The ABPS was found to be valid, although pictures without context might be preferable for measuring cognitive biases than pictures with context. We discuss how an explicit approach to picture construction may aid in creating variations of the ABPS. Finally, we describe how ABPS adoption across studies may allow more reproducible and comparable results across paradigms, while allowing researchers to apply picture selection criteria that correspond to a wide range of theoretical positions. The latter is exemplified by ABPS derivatives and adoptions that are currently under way.